Diverse genetic aetiologies and clinical outcomes of paediatric hypoparathyroidism. (19th October 2015) - Kim, Ja Hye; Shin, Young‐Lim; Yang, Seung; Cheon, Chong Kun; Cho, Ja Hyang; Lee, Beom Hee; Kim, Gu‐Hwan; Lee, Jin Ok; Seo, Eul Joo; Choi, Jin‐Ho; Yoo, Han‐Wook
Summary: Context: Hypoparathyroidism is characterized by hypocalcaemia, hyperphosphataemia, and low or inappropriately normal parathyroid hormone (PTH) levels. Idiopathic or genetic drivers are the predominant causes of hypoparathyroidism in paediatric‐age patients. Objective: This study investigated the aetiology and clinical course of primary hypoparathyroidism in infancy and childhood. Subjects and measurements: This study included 37 patients (23 males, 14 females) with primary hypoparathyroidism diagnosed prior to 18 years of age. We analysed aetiologies, initial presentation, age at diagnosis, endocrine and radiological findings, and outcomes. Results: The median age at presentation was 1·7 months (range 1 day–17 years), and the mean follow‐up duration was 7·0 ± 5·3 years (range 0·5–16·8 years). Our cohort included 22 cases (59·5%) of 22q11·2 microdeletion syndrome. Other aetiologies included hypoparathyroidism–deafness–renal dysplasia syndrome (5/37, 13·5%) and one patient each with autoimmune polyglandular syndrome type 1, Kearns–Sayre syndrome and Kenny–Caffey syndrome. The remaining 7 (18·9%) patients were classified as idiopathic hypoparathyroidism cases. Among the 15 patients who underwent brain imaging, 5 (33·3%) had basal ganglia calcification. Among the 26 patients examined by renal imaging, 5 (19·2%) had either nephrocalcinosis or a renal stone. After 11 months of calcium or calcitriol supplementation, 16 patients (43·2%) discontinued medication. The final PTH levels were significantly higher in patients with transient hypoparathyroidism than those with permanent hypoparathyroidism. Conclusions: Identification of the genetic aetiologies of hypoparathyroidism makes it possible to predict patient outcomes and provide appropriate genetic counselling. Long‐term treatment with calcium and calcitriol necessitates monitoring for renal complications.